1984
DOI: 10.1007/bf01041352
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for the DNA base specificity of light-induced banding

Abstract: Experiments have been carried out to investigate the DNA base specificity of light-induced banding (LIB) produced by photo-oxidation of chromosomes followed by Acridine Orange staining to detect denatured DNA. Nuclei of different base composition, human and onion, and fluorochromes of different base specificities and modes of binding to DNA were used. Our results indicate that specific destruction of guanine residues is the main effect of photo-oxidation under the conditions used, and that LIB is a base-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The possible photodenaturation of DNA was suggested previously by others (25,26,27). It has been suggested that denaturation of DNA might occur as a result of photosensitized oxidation of guanine in fixed cells and isolated DNA (27,28,29). However, these authors did not demonstrate that the light-induced changes in chromatographic DNA mobility (27) or staining pattern of mitotic chromosomes (25,26) that they observed were due to a transition between ds and ss DNA.…”
Section: Discussionmentioning
confidence: 83%
“…The possible photodenaturation of DNA was suggested previously by others (25,26,27). It has been suggested that denaturation of DNA might occur as a result of photosensitized oxidation of guanine in fixed cells and isolated DNA (27,28,29). However, these authors did not demonstrate that the light-induced changes in chromatographic DNA mobility (27) or staining pattern of mitotic chromosomes (25,26) that they observed were due to a transition between ds and ss DNA.…”
Section: Discussionmentioning
confidence: 83%
“…The possible photodenaturation of DNA was suggested previously by others (25,26,27). It has been suggested that denaturation of DNA might occur as a result of photosensitized oxidation of guanine in fixed cells and isolated DNA (27,28,29). However, these authors did not demonstrate that the light‐induced changes in chromatographic DNA mobility (27) or staining pattern of mitotic chromosomes (25,26) that they observed were due to a transition between ds and ss DNA.…”
Section: Discussionmentioning
confidence: 99%